2014
DOI: 10.5014/ajot.2014.013581
|View full text |Cite
|
Sign up to set email alerts
|

Update on Productive Aging Research in the American Journal of Occupational Therapy, 2013, and Overview of Research Published 2009–2013

Abstract: In light of the Centennial Vision charge of supporting practice through evidence, this article reviews productive aging research published in the American Journal of Occupational Therapy (AJOT) in 2013 and as a whole from 2009 to 2013. Thirteen such articles were published in 2013, consisting of 4 systematic reviews that identified effective occupational therapy interventions for older adults with low vision; 1 randomized controlled trial that examined changes in occupational therapists' mental health practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Although the CAPABLE model by design employs occupational therapists to treat older adults with physical disability who are cognitively intact, occupational therapists have been core members of in‐home, multidisciplinary teams for older adults with dementia and their family caregivers in successful randomized trials . Productive aging is a rapidly growing area of research and practice in the occupational therapy profession, and many studies have demonstrated the value of interventions with older adults when occupational therapists are core team members . Stronger, more‐targeted collaborations between geriatricians and occupational therapists would help accelerate dissemination of successful evidence‐based in‐home care models focused on function of older adults with or without neurocognitive impairment.…”
Section: Organizational Considerationsmentioning
confidence: 99%
“…Although the CAPABLE model by design employs occupational therapists to treat older adults with physical disability who are cognitively intact, occupational therapists have been core members of in‐home, multidisciplinary teams for older adults with dementia and their family caregivers in successful randomized trials . Productive aging is a rapidly growing area of research and practice in the occupational therapy profession, and many studies have demonstrated the value of interventions with older adults when occupational therapists are core team members . Stronger, more‐targeted collaborations between geriatricians and occupational therapists would help accelerate dissemination of successful evidence‐based in‐home care models focused on function of older adults with or without neurocognitive impairment.…”
Section: Organizational Considerationsmentioning
confidence: 99%